Aseptic meningitis in a child due to 2009 pandemic influenza A (H1N1) infection - Ozdemir, Halil; Karbuz, Adem; Ciftçi, Ergin; Ince, Erdal; Doğru, Ulker (The Turkish Journal of Pediatrics, 2011)
Neurologic manifestations of seasonal influenza 2009 pandemic influenza A (H1N1) are now known to include encephalitis, acute disseminated encephalomyelitis, Guillain-Barré syndrome, transverse myelitis, and acute necrotizing encephalopathy. We report a case of 2009 pandemic influenza A (H1N1) meningitis in a previously healthy six-year-old girl who presented with fever, headache, abdominal pain, and vomiting. The infection was confirmed via nasopharyngeal and throat swabs. She was treated with oseltamivir successfully. To our knowledge, she is the first child diagnosed as pandemic influenza A (H1N1) meningitis.